Maternal Folate Intake during Pregnancy and Childhood Asthma in a Population-based Cohort - Parr, Christine L.; Magnus, Maria C.; Karlstad, Øystein; Haugen, Margaretha; Refsum, Helga; Ueland, Per M.; McCann, Adrian; Nafstad, Per; Håberg, Siri E.; Nystad, Wenche; London, Stephanie J. (American journal of respiratory and critical care medicine, 2017)
A potential adverse effect of high folate intake during pregnancy on children's asthma development remains controversial. To prospectively investigate folate intake from both food and supplements during pregnancy and asthma at age 7 years when the diagnosis is more reliable than at preschool age. This study included eligible children born 2002-2006 from the Norwegian Mother and Child Cohort Study, a population-based pregnancy cohort, linked to the Norwegian Prescription Database. Current asthma at age 7 was defined by asthma medications dispensed at least twice in the year (1,901 cases; n = 39,846) or by maternal questionnaire report (1,624 cases; n = 28,872). Maternal folate intake was assessed with a food frequency questionnaire validated against plasma folate. We used log-binomial and multinomial regression to calculate adjusted relative risks with 95% confidence intervals. Risk of asthma was increased in the highest versus lowest quintile of total folate intake with an adjusted relative risk of 1.23 (95% confidence interval, 1.06-1.44) that was similar for maternally reported asthma. Mothers in the highest quintile had a relatively high intake of food folate (median, 308; interquartile range, 241-366 μg/d) and nearly all took at least 400 μg/d of supplemental folic acid (median, 500; interquartile range, 400-600 μg/d). In this large prospective population-based cohort with essentially complete follow-up, pregnant women taking supplemental folic acid at or above the recommended dose, combined with a diet rich in folate, reach a total folate intake level associated with a slightly increased risk of asthma in children.